Interleukin-33 Induces the Enzyme Tryptophan Hydroxylase 1 to Promote Inflammatory Group 2 Innate Lymphoid Cell-Mediated Immunity - Flamar, Anne-Laure; Klose, Christoph S.N.; Moeller, Jesper B.; Mahlakõiv, Tanel; Bessman, Nicholas J.; Zhang, Wen; Moriyama, Saya; Stokic-Trtica, Vladislava; Rankin, Lucille C.; Putzel, Gregory Garbès; Rodewald, Hans-Reimer; He, Zhengxiang; et al. (Immunity (Cambridge, Mass.), 2020)
Group 2 innate lymphoid cells (ILC2s) regulate immunity, inflammation, and tissue homeostasis. Two distinct subsets of ILC2s have been described: steady-state natural ILC2s and inflammatory ILC2s, which are elicited following helminth infection. However, how tissue-specific cues regulate these two subsets of ILC2s and their effector functions remains elusive. Here, we report that interleukin-33 (IL-33) promotes the generation of inflammatory ILC2s (ILC2INFLAM) via induction of the enzyme tryptophan hydroxylase 1 (Tph1). Tph1 expression was upregulated in ILC2s upon activation with IL-33 or following helminth infection in an IL-33-dependent manner. Conditional deletion of Tph1 in lymphocytes resulted in selective impairment of ILC2INFLAM responses and increased susceptibility to helminth infection. Further, RNA sequencing analysis revealed altered gene expression in Tph1 deficient ILC2s including inducible T cell co-stimulator (Icos). Collectively, these data reveal a previously unrecognized function for IL-33, Tph1, and ICOS in promoting inflammatory ILC2 responses and type 2 immunity at mucosal barriers. •IL-33 promotes inflammatory ILC2s•Tph1 is upregulated in ILC2s upon activation in an IL-33-dependent manner•Il7rCre/+Tph1flox/flox mice are highly susceptible to helminth infections•Tph1 regulates inflammatory ILC2 responses during helminth infection IL-33 is a potent activator of type 2 immune responses via the stimulation of ILC2s, but the downstream pathways triggered in these cells are poorly defined. Flamar and colleagues show that IL-33 controls tryptophan hydroxylase 1 expression in ILC2s, which is required for type 2 immunity against worm infections.